The Implementation of Educational Oversight to Improve Teacher Performance and the Quality of Education in Islamic Boarding Schools - Zainab; Ahmad Masruhan Zakariya (Tahta Media Group, 2026)
This study aims to describe and analyze the implementation of educational supervision in improving teacher performance and the quality of education at the Nashrus Sunnah Islamic Boarding School, Madiun City. The method applied in this study is qualitative with a focus on case studies. Data was collected through interviews, observations, and data analysis related to teacher development programs. Information analysis was carried out by applying the Miles and Huberman model which consisted of data reduction, data presentation, and conclusion drawing to obtain valid and comprehensive results. The results of this study used the interview method, consisting of the main parts that are in accordance with the research objectives, including 1. Planning and pre-observation, 2. observation and supervision, 3 Supervision of administration, and 4. evaluation and feedback. The findings obtained from this study show that supervision at the Nashrus Sunnah Islamic Boarding School is carried out systematically through regular academic, clinical, and coaching supervision. This supervision has been proven to be able to improve teachers' skills in compiling teaching materials, choosing more varied methods, and improving classroom management and learning assessment. Furthermore, this supervision has a positive impact on the quality of education, which can be seen from the increase in student participation and the effectiveness of the teaching and learning process. This study concludes that the implementation of educational supervision at Nashrus Sunnah Islamic Boarding School has been proven to be significant for improving teacher performance and overall quality of education.